Job Insecurity and Workload: Does Stress Lead to Cyberloafing? - N. Lilis Suryani; Rahmi Hermawati; Muhamad Guruh (Goodwood Publishing, 2026)
Purpose: This study aimed to examine the effects of job insecurity and workload on cyberloafing behavior among hospital security guards, with job stress as a mediating variable. Research Methodology: This study employed a quantitative survey approach involving all 155 security guards assigned to ten hospitals in South Tangerang using a saturated sampling technique. Data were collected through structured questionnaires and analyzed using SmartPLS. Results: The results show that Job insecurity had a positive and significant effect on cyberloafing behavior and job stress. Workload also significantly influences cyberloafing behavior and job stress. Job stress had a significant effect on cyberloafing behavior and partially mediated the relationship between job insecurity and cyberloafing. However, job stress did not mediate the relationship between workload and cyberloafing, indicating that workload directly influences cyberloafing. Conclusions: Job stress plays a significant role in linking job insecurity to cyberloafing behavior among hospital security guards, whereas workload contributes directly to cyberloafing, regardless of stress levels. Limitations: This study was limited to security guards working in ten hospitals in South Tangerang, which may restrict the generalizability of the findings. In addition, this study examined only job insecurity, workload, and job stress as predictors of cyberloafing behavior. Contributions: This study contributes to the organizational behavior literature by clarifying the mediating role of job stress and providing practical implications for hospital management in managing job insecurity and workload to reduce cyberloafing behavior.